Perspektif ibu bapa terhadap permasalahan dan cabaran dalam pembentukan nilai murni pelajar - Othman, Mohammad Khairi; Mohd Yusoff, Mohd Zailani; Abdul Rahim, Fauziah; Puteh, Alis; Kasa, Muhamad Dzahir; Roslan, Nur Fasihah (Universiti Teknologi Malaysia, 2016)
This study aims to examine parents’ perspective towards issues and challenges in developing good values among secondary school students.This descriptive-survey study was conducted on a few respondents comprised of parents, through interviews, in one the states in Malaysia.This study found that the issue faced by parents is related to family relationship factors such as limited time spent with children, preference of children to share problems or stories with other people, parents’ attitudes and children’s own attitudes.Meanwhile, challenges faced by parents are children’s peer influence and excessive use of technology.In conclusion, issues and challenges presented in this study are significant and should be made aware so that children can be molded at early stages to become future successors.Parenting skill is vital to ensure peace and harmony in the family.Good tutelage and support should be provided to the children according to their age so that there will be positive reception and feedback.